APPLICATION OF THE CONDITIONED REVERSE PATH METHOD - GARIBALDI, L. (Mechanical systems and signal processing, 2003)
The conditioned reverse path (CRP) method has been applied to identify the non-linear behaviour of a beam-like structure, both ends clamped, one with a non-linear stiffness characteristic. The same method was already successfully applied to the identification of another COST benchmark, known as the VTT non-linear suspension. This benchmark shows the enhancements of the technique, now applied to a real multi-degree-of-freedom (mdof) system, with single-point excitation subject to bending modes; the non-linearity is acting on one end of the beam in terms of displacements. The CRP technique is based on the construction of a hierarchy of uncorrelated response components in the frequency domain, allowing the estimation of the coefficients of the non-linearities away from the location of the applied excitation and also the identification of the linear dynamic compliance matrix when the number of excitations is smaller than the number of response locations.